Susceptibility profile of blaOXA-23 and metallo-β-lactamases co-harbouring isolates of carbapenem resistant Acinetobacter baumannii (CRAB) against standard drugs and combinations - Sharma, Swati; Banerjee, Tuhina; Yadav, Ghanshyam; Kumar, Ashok (Frontiers in Cellular and Infection Microbiology, 2023)
Background The rapid emergence of carbapenem resistant Acinetobacter baumannii (CRAB) has resulted in an alarming situation worldwide. Realizing the dearth of literature on susceptibility of CRAB in genetic context in the developing region, this study was performed to determine the susceptibility profile against standard drugs/combinations and the association of in-vitro drug synergy with the prevalent molecular determinants. Methods and findings A total of 356 clinical isolates of A. baumannii were studied. Confirmation of the isolates was done by amplifying recA and ITS region genes. Susceptibility against standard drugs was tested by Kirby Bauer disc diffusion. Minimum inhibitory concentration (MIC), MIC50 and MIC90 values against imipenem, meropenem, doripenem, ampicillin/sulbactam, minocycline, amikacin, polymyxin B, colistin and tigecycline was tested as per guidelines. Genes encoding enzymes classes A (blaGES, blaIMI/NMC-A, blaSME, blaKPC), B (blaIMP, blaVIM, blaNDM) and D (blaOXA-51,blaOXA-23 and blaOXA-58) were detected by multiplex polymerase chain reaction. Synergy against meropenem-sulbactam and meropenem-colistin combinations was done by checkerboard MIC method. Correlation of drug synergy and carbapenemase encoding genes was statistically analyzed. Results Of the total, resistance above 90% was noted against gentamicin, ciprofloxacin, levofloxacin, ceftazidime, cefepime, ceftriaxone, cotrimoxazole and piperacillin/tazobactam. By MIC, resistance rates from highest to lowest was seen against imipenem 89.04% (n=317), amikacin 80.33% (n=286), meropenem 79.49% (n=283), doripenem 77.80% (n=277), ampicillin/sulbactam 71.62% (n=255), tigecycline 55.61% (n=198), minocycline 14.04% (n=50), polymyxin B 10.11% (n=36), and colistin 2.52% (n=9). CRAB was 317 (89.04%), 81.46% (n=290) were multidrug resistant and 13.48% (n=48) were extensively drug resistant. All the CRAB isolates harboured blaOXA-51 gene (100%) and 94% (n=298) blaOXA-23 gene. The blaIMP gene was most prevalent 70.03% (n=222) followed by blaNDM, 59.62% (n=189). Majority (87.69%, 278) were co-producers of classes D and B carbapenemases, blaOXA-23 with blaIMP and blaNDM being the commonest. Synergy with meropenem-sulbactam and meropenem-colistin was 47% and 57% respectively. Reduced synergy (p= <0.0001) was noted for those harbouring blaOXA-51+blaOXA-23with blaNDM gene alone or co-producers. Conclusion Presence of blaNDM gene was a significant cause of synergy loss in meropenem-sulbactam and meropenem-colistin. In blaNDM endemic regions, tigecycline, minocycline and polymyxins could be viable options against CRAB isolates with more than one carbapenemase encoding genes.